2019
DOI: 10.1002/ente.201800539
|View full text |Cite
|
Sign up to set email alerts
|

CdS Quantum Dots Sensitized 2D La2Ti2O7 Nanosheets as Support for Visible Light‐Assisted Electrocatalytic Methanol Oxidation in Alkaline Medium

Abstract: The heterojunction of cadmium sulfide (CdS)/La2Ti2O7 (CdS/LTO) attracts great attention in the application of photocatalysis. Here, it is used as a visible light–activated support and extends to the application of direct methanol fuel cells (DMFCs). First, uniform CdS quantum dots (QDs) are deposited on the surface of 2D perovskite‐type LTO nanosheets to form the CdS QDs/LTO heterojunction. Then, Pt electrocatalysts are deposited on the as‐prepared CdS QDs/LTO heterojunction and used as a working electrode for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…As shown in Figure B, the degree of fluorescent quenching of TCPP–CoS is greater than that of CoS. The efficient PL quenching means that TCPP–CoS can effectively inhibit the electron–hole recombination, indicating that the photogenerated electrons generated by excited porphyrins are efficiently trapped by CoS …”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…As shown in Figure B, the degree of fluorescent quenching of TCPP–CoS is greater than that of CoS. The efficient PL quenching means that TCPP–CoS can effectively inhibit the electron–hole recombination, indicating that the photogenerated electrons generated by excited porphyrins are efficiently trapped by CoS …”
Section: Resultsmentioning
confidence: 96%
“…As shown in Figure 6B, the degree of fluorescent quenching of TCPP−CoS is greater than that of CoS. The efficient PL quenching means that TCPP− CoS can effectively inhibit the electron−hole recombination, indicating that the photogenerated electrons generated by excited porphyrins are efficiently trapped by CoS. 46 Figure 6C displays the UV−vis diffuse reflectance spectra (DRS) of CoS and TCPP−CoS, respectively. The same amounts of both catalysts were used in the UV/Vis diffuse reflection experiments.…”
Section: Resultsmentioning
confidence: 97%
“…The high dispersion of CdS has been confirmed that can boost the photo/electrocatalytic activity. [ 17 ]…”
Section: Resultsmentioning
confidence: 99%
“…When reacts with the OH À /H 2 O on the catalyst, h þ potential is just able to form a hydroxyl radical (•OH) with the OH À . [42,43] Subsequently, the e À is transferred to RGO and then to the electrode. The •OH has highly oxidizing property and can oxidize substances (e.g., methanol molecules) adsorbed on the electrode surface.…”
Section: Resultsmentioning
confidence: 99%